Ketika Jurnalisme Memproduksi Cerita Horor - Razali, Geofakta; Wirawan, Wirawan (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
TThis research aims to investigate the production of horror contents in the INSENTIF podcast channel by Tirto.id, an Indonesian online news media. When journalistic media are involved in the production of ghost stories and mystery, it raises concerns about journalistic basic principles of providing verified information. To understand this phenomenon, we conducted a qualitative case study and interviewed three key informants from the INSENTIF production team. Using Giddens’ structuration theory as an analysis framework, we identify that the INSENTIF production crews still perceive their routine as part of journalistic works. In writing the script, they strive to rely on credible sources and actualise the discipline of verification although they admit that they insert some fictional horrific scenarios at the beginning of each episode as well. Thus, they mention a disclaimer, explaining that their journalism practice, specifically on horror episodes, is not the same as the regular Tirto.id’s standard journalism. This research argues that the agents, in this case, seem to follow and reproduce the existing structure, rather than resist it.